Analisis Kecurangan Laporan Keuangan PT Asuransi Jiwasraya dengan Analisis Fraud Pentagon - Rizka Haryanti (Sanskara Akuntansi dan Keuangan, 2023)
The risk of fraud in the financial statements is a risk that will always exist as a result of disclosing misstatements borne by the Company's management. PT Asuransi Jiwasraya went bankrupt and failed to pay. The purpose of this study is to identify fraudulent financial statements from Jiwasraya using the pentagon fraud theory. The pentagon fraud theory is a theory developed from Cressey's 1953 fraud triangle theory. The five elements of risk are: pressure; chance; rationalization; Need; arrogance. The method used in this research is a quantitative descriptive method. PT Asuransi Jiwasraya (Persero) lost investment funds for the JS Saving Plan product due to being unable to pay interest and customer investment funds. PT. Asuransi Jiwasraya officially closed on May 31 2021 and was transferred to PT Asuransi Jiwa IFG (IFG Life).